The father’s age is six times his son’s age. Four years hence, the age of the father will be four times his son’s age. The present ages (in year) of the son and the father are, respectively.

Let ‘x’ year be the present age of father and ‘y’ year be the present age of son.

Four years hence, it has relation by given condition,

(x+4) = 4(y+4)

x+4 = 4y+16

x- 4y-12 = 0 …(i)

and initially, x = 6y …(ii)

On putting the value of from Eq. (ii) in Eq. (i), we get

6y - 4y - 12 = 0

2y = 12

Hence, y = 6

Putting y = 6, we get x = 36.

Hence, present age of father is 36 years and age of son is 6 years.